THE EFFECT OF EXERCISES OF DUTIES AND TACTICAL PRINCIPLES OF AN OFFENSIVE AND DEFENSIVE COMPOSITE ACCORDING TO SPECIFIC SPACES IN DEVELOPING THE SPEED AND ENDURANCE OF SKILL PERFORMANCE - Dheyaa Salim Hafedh (Journals Park Publishing, 2023)
The purpose of the study was to determine the application of the effect of duties exercises and the principles of offensive and defensive complex tactics in developing the speed and endurance of skill performance. The researcher utilised an experimental design. The research sample consisted of twenty-four (24) Naft Misan Club players randomly divided into two experimental and control groups of twelve (12) players, each using a straight random draw. The researcher used the statistical programme (SPSS), and the most significant findings were that the method of training Alawa meals and the principles of offensive and defensive complex tactics according to specific spaces have a positive effect on reducing the time and effort required to develop capabilities and skills separately and applying the exercises of duties and tactical principles of the offensive and defensive complex to specific spaces in a larger size due to their positive impact that serves all performance requirements
Keywords: Exercises, Principles, Offensive, Defensive Composite, Speed, Endurance Performance.